The Association Between Educational Achievements, Career Aspirations, Achievement Motives and Oral Hygiene Behavior among Dental Students of Udaipur, India - Asawa, Kailash (Ethiop J Health Sci, 2014)
BACKGROUND: There are several factors which influence oral hygiene behavior of an individual. Educational achievements, career aspirations and achievement motives of individuals are some of those factors. The objective of this study was to investigate whether educational achievements, career aspirations and achievement motives have associations with oral hygiene behavior among dental students of Udaipur, India. METHODS: A descriptive cross-sectional study was conducted among all (n=200) 1(st) year dental students from all dental colleges of Udaipur City, India. Self-administered structured questions were used to assess their educational achievements, career aspirations and oral hygiene behavior (OHB). Achievement motives were assessed using Achievement Motive Scale developed by Lang and Fries (2006). Chi-square test and multivariate logistic regression tests were used in data analysis. Confidence level and level of significance were set at 95% and 5% respectively. RESULTS: Students with better educational achievements undergone regular dental check-up (30.48%) (p=0.03) and used other oral hygiene aids (90.24%) (p=0.01). Tooth brushing frequency, time and replacement time of tooth brush were found to be significantly associated with career aspiration (p=0.007; p=0.002; p=0.00 respectively). Achievement motives did not have statistically significant association with oral hygiene behavior. CONCLUSION: Educational achievements and career aspirations appear to be associated with oral hygiene behavior of young dental students. Students with higher career aspirations practiced better oral hygiene behavior. There was no significant relationship between achievement motives and oral hygiene behavior.